THE SAME DOMESTIC NUMBER OF COURTS NORMATIVE LEGAL BASIS (Journal of actual problems of jurisprudence, 2019)
In given article are considered questions, concerning normative actual основ of the shaping the internal belief to judges oncriminal deals.